Antitropomotphology of musculus flexor carpi radialis in fetuses - Jaśkowski, January; Kołaczkowski, Zdzisław (Anthropological Review, 1975)
After dissection of 16 male and 16 female fetuses (crown rump length ranging from 155 to 340 mm) m. flexor carpi radialis was examined anthropometrically. Characteristics of adult morphology were found.Mean length of the fleshy part is 14.65% of crown-rump length and relatively increases with age of fetuses. Part of the tendon lying above joint is smaller in males and relatively decreases with age. No distinct sex and age differences in proportions of the muscle were observed.